Liver transplantation for iatrogenic bile duct injury during cholecystectomy: a French retrospective multicenter study. Issue 1 (January 2022) - Chiche, Laurence; Guieu, Maxime; Bachellier, Philippe; Suc, Bertrand; Soubrane, Olivier; Boudjema, Karim; Navarro, Francis; Adam, René; Vaillant, Jean-Christophe; Salame, Ephrem; Heyd, Bruno; Truant, Stéphanie; et al.
Abstract: Background: Major bile duct injuries (BDI) following cholecystectomy require complex reconstructive surgery. The aim was to collect the liver transplantations (LT) performed in France for major BDI following cholecystectomy, to analyze the risk factors and to report the results. Methods: National multicenter observational retrospective study. All the patients who underwent a LT in France between 1994 and 2017, for BDI following cholecystectomy, were included. Results: 30 patients were included. 25 BDI occurred in non hepato-biliary expert centers, 20 were initially treated in these centers. Median time between injury and LT was 3 years in case of an associated vascular injury (11 injuries), versus 11.7 years without vascular injury (p = 0.006). Post-transplant morbidity rate was 86.7%, mortality 23.5% at 5 years. Conclusion: Iatrogenic BDI remains a real concern with severe cases, associated with vascular damages or leading to cirrhosis, with no solution but LT. It is associated with high morbidity and not optimal results. This enlights the necessity of early referral of all major BDI in expert centers to prevent dramatic outcome. Decision to perform transplantation should be taken before dismal infectious situations or biliary cirrhosis and access to graft should be facilitated by Organ Sharing Organizations.